On The Relationship Between The Gospel And Culture In Selected Works Of Giuseppe Maria Zanghí - Ciećko, Szymon Krzysztof (Studia Theologica Varsaviensia, 2018)
The article addresses the issue of understanding of culture in the light of the so-called Trinitarian ontology. Giuseppe Maria Zanghí, a ontemporary, who died two years ago, is an Italian philosopher and theologian sociated with Chiara Lubich and the Focolare Movement founded by her. The key elements are the analysis of the events of Christ – from the Incarnation to the Cross, as well as the Resurrection after it. This article discusses the criticism of ontology by G.M. Zanghí, his proposal to recreate this branch of science and its possible consequences for the Western culture. O relacji między Ewangelią a kulturą w wybranych publikacjach Giuseppe Marii Zanghiego - Streszczenie W artykule poruszono zagadnienie rozumienia kultury w świetle tak zwanej ontologii trynitarnej. Taką refleksję proponuje Giuseppe Maria Zanghí, współczesny – zmarły przeszło dwa lata temu – włoski filozof i teolog, związany z Chiarą Lubich oraz ufundowanym przez nią Ruchem Focolare. Elementami kluczowymi są analiza wydarzenia Chrystusa – od Inkarnacji aż do opuszczenia na krzyżu, jak również następującego po nim Zmartwychwstania. W artykule omawia się krytykę ontologii dokonaną przez G.M. Zanghiego, jego propozycję rekonstrukcji tej gałęzi nauki oraz możliwe jej konsekwencje dla kultury zachodniej.